A Spectrum Sensing Method for TDM based Cognitive Radio Networks - Satyanarayana, D; Said Alkalbani, Abdullah (International Journal of Engineering and Technology, 2018)
The usage of mobile radio devices has been increased exponentially for the last few years and the radio spectrum is being exhausted every day. Hence, there is huge demand for new methods and technologies for solving the radio spectrum scarcity. On this line, the researchers invented a new technology called Cognitive Radio Networks (CRN). There are two phases associated with the CRN. The first phase handles the spectrum hole detection and the second phase allocates the spectrum hole. In this paper, we propose a new method for spectrum hole detection in time division multiplexing (TDM) based communications systems. The simulation work shows that the proposed method is useful for solving the spectrum scarcity problems in TDM based systems.Â Â Â